Seismic fragility analysis of fully prefabricated frame structures with steel plate hoop bolt connections based on various engineering demand parameters - Zhiyuan Gao; Jiaolei Zhang; Lei Cao (PLoS ONE, 2026)
Steel plates and bolted connections have become common construction details in prefabricated structural systems. However, prefabricated frame structures with steel plate hoop–bolted connections exhibit connection gaps, interface slip, and discontinuous force-transfer paths, making them prone to hysteretic degradation and cumulative damage under seismic loading. Conventional seismic fragility assessments typically rely on the maximum inter-story drift ratio, which focuses only on deformation demand and fails to capture key deterioration mechanisms such as low-cycle damage accumulation, stiffness degradation, and reduced energy dissipation capacity. Consequently, the seismic performance of prefabricated structures may be inadequately represented. To address this limitation, this study adopts a two-parameter damage model as the engineering demand parameter for incremental dynamic analysis (IDA) and fragility assessment, and compares it with the traditional drift-based index. An energy-dissipation-based story damage weighting method is further introduced to better characterize damage distribution and performance degradation along the structural height. Finite element models of prefabricated columns and beam–column joints with steel plate hoop–bolted connections were developed in SAP2000 using multilinear plastic link elements and validated against quasi-static test results. A comparative fragility analysis was then performed for six-story full prefabricated and cast-in-place frame structures. The results show that the inter-story drift ratio underestimates structural capacity in the elastic stage but overestimates collapse resistance compared with the two-parameter damage model.